2013
DOI: 10.1002/jcp.24370
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchange is inactivated during mouse oocyte meiosis, facilitating glycine accumulation that maintains embryo cell volume

Abstract: The coupled action of the Na(+)/H(+) exchanger NHE1 and the HCO3(-)/Cl(-) exchanger AE2 constitutes the principal mechanism for acute correction of decreased cell volume in mammalian somatic cells, while, when acting separately, they regulate intracellular pH. It was previously found that AE2 becomes inactivated during meiosis in mouse oocytes. Similarly, NHE1 activity stimulated by intracellular acidosis was present in preovulatory germinal vesicle stage (GV) mouse oocytes and then decreased during meiotic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(130 reference statements)
0
8
0
1
Order By: Relevance
“…We first determined whether maximally inhibiting FAK would affect the ability of 2-cell embryos to activate NHE1 in response to a cell volume decrease. These experiments relied on our previously validated assay that detects volume-mediated increases in NHE1 activity as a marked intracellular alkalinization when cell volume is decreased by introduction of hypertonic medium (Zhou & Baltz, 2013; Zhou et al , 2013; Xu et al , 2017). We used the selective FAK inhibitor PF-562271 at a high concentration that would be expected to completely block any FAK activity (Roberts et al , 2008) and that was similar to concentrations previously used to inhibit FAK in other types of intact cells (Wiemer et al , 2013; Yoon et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We first determined whether maximally inhibiting FAK would affect the ability of 2-cell embryos to activate NHE1 in response to a cell volume decrease. These experiments relied on our previously validated assay that detects volume-mediated increases in NHE1 activity as a marked intracellular alkalinization when cell volume is decreased by introduction of hypertonic medium (Zhou & Baltz, 2013; Zhou et al , 2013; Xu et al , 2017). We used the selective FAK inhibitor PF-562271 at a high concentration that would be expected to completely block any FAK activity (Roberts et al , 2008) and that was similar to concentrations previously used to inhibit FAK in other types of intact cells (Wiemer et al , 2013; Yoon et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…For pHi measurements, decreased cell volume was induced with 350 mOsM medium. We previously showed that the rate of pHi increase was robust at both 350 and 550 mOsM (Zhou et al , 2013). For western blots, we had previously shown for JAK2 that phosphorylation was more easily detected at 550 than 350 mOsM (Zhou & Baltz, 2013).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…En effet, sa supplémentation dans les milieux de culture favorise la maturation de l'ovocyte chez la vache, le hamster, le chien, le lapin et le singe. Enfin, chez la souris, la glycine est impliquée dans la régulation du volume de l'ovocyte au cours de l'ovulation (Zhou et al 2013).…”
Section: A) Cellules Folliculairesunclassified
“…Glycine replaces inorganic ions that are instrumental in acute control of cell volume in the early embryo but are detrimental in the longer term 8 . Since early mammalian embryos are extremely sensitive to cell size perturbations, the failure of glycine-mediated cell volume control leads to developmental arrest 911 .…”
Section: Introductionmentioning
confidence: 99%